Multicultural Work in Five United Nations Organisations: An Austrian Perspective - Dagmar Kiefer (Peter Lang International Academic Publishers, 2009)
This book aims at developing an understanding of multicultural work in five Organisations of the United Nations. The context of international organisations differs from international companies, amongst others, with regards to the legal base, the financial and operational agenda, and human resource practices. The purpose of this study is to explore which factors are a trigger, a barrier, and/or an influence on team and group work in this specific context. Based on 50 semi-structured, personal interviews which were analysed within the framework of constant comparison method, a typology of multicultural work is provided. Moreover, this study offers an integrative view of the reciprocal relationships between organisation, management, group and individual.
Keywords: 330